KONSEP MASLAHAH PERSPEKTIF IZZUDIN IBN ABD. SALAM (Telaah dalam Kitab Qawa`id al-Ahkam fi Masalih al-Anam) - Nugroho, Irzak Yuliardy; Hamidah, Tutik (Ulumuna: Jurnal Studi Keilsman, 2021)
It has become a belief that the rules of law in the Shari'a have one noble goal, namely to obtain goodness and benefit for humans, and avoid harm. Finally, it demands the scholars from the jurists, ushuliyyun, and Muslim scholars to always develop their studies and thoughts for the purpose of the Shari'a. Muslim figures such as Syatibi, Najmuddin at-Tufi, Jasser Auda, Ahmed an-Na'im, M. Syahrur, Khalid Abu el-Fadhl, and including Izzudin bin Abd. Salam has been trying to make efforts to float. One of the scientific developments in the methodological aspect seems to be a trend that does not die. This paper is a study of the thoughts of a character, namely Izzudin bin Abd. Greetings with a qualitative-descriptive method and using a library research approach contained in the book Qawa`id al-Ahkam fi Mashalih al-Anam. The conclusion of this book is that maslahah contains three dimensions, namely ladzat, afrakh and everything that mediates between the two. Furthermore, he emphasizes the maslahah aspect of distinguishing between something that is real and majazi, which in the next stage leads to the benefit of the world and the benefit of the hereafter.